Piezoelectric materials - Lopes, Vicente [UNESP]; Marqui, Clayton Rodrigo (Springer Nature, 2016)
Piezoelectricity is a phenomenon in which certain crystalline substances develop an electric field when subjected to pressure force, or conversely, exhibit a mechanical deformation when subjected to an electric field. This reciprocal cou- pling between mechanical and electrical energy provides useful features for these materials. The dynamics of the piezoelectric sensor/actuator plays an increasing importance when higher performance from closed loop systems or damage moni- toring is required for strategic applications. This chapter focuses on the develop- ment of the constitutive equations of smart structures. The incorporation of mass, stiffness, and electromechanical coupling of the piezoceramic patches has a signif- icant influence on the dynamics properties of the system.
Keywords: Electromechanical coupling; Piezoelectric material; Smart structure